IMPLEMENTASI SERVICE RECOVERY DALAM PENANGANAN KELUHAN PADA INDUSTRI PERHOTELAN (STUDI KASUS PADA HOTEL COURTYARD HOTEL) - I Wayan Kiki Sanjaya (CV. Lafadz Jaya, 2026)
This study aims to analyze the implementation of service recovery in handling guest complaints within the hospitality industry, using Courtyard Hotel as a case study. The primary focus is to identify the types of complaints submitted by guests via the TripAdvisor platform and to analyze the handling strategies implemented by hotel stakeholders. The research method employed is descriptive qualitative. Data were collected through observations of online reviews on TripAdvisor from March 2021 to December 2022, semi-structured interviews with the Front Desk Manager, and documentation studies. Data analysis techniques followed the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. The results indicate five categories of guest complaints: 1) Mechanical Complaints regarding physical facilities such as air conditioning and hot water; 2) Attitudinal Complaints regarding staff behaviour, particularly in the security department; 3) Service-Related Complaints regarding operational service standards; 4) Unusual Complaints, which are subjective and based on individual guest preferences ; and 5) Emotional Complaints, which arise when guests feel undervalued during large-scale events at the hotel. Complaint handling strategies at Courtyard Hotel are implemented through two channels: online and direct. Online handling follows an SOP for resolution within 3x24 hours , while direct handling applies the